Strategi Kepala Sekolah Dalam Pembentukan Karakter Siswa Melalui Program Keagamaan - Hartini, Lelly Adi; Faza, Najmi (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2025)
Shaping student character is certainly the most important goal for principals to do., and every principal's leadership must have its own strategy in developing it. MTs Mabdaul Falah West Kaduara Educational Institution implements a religious program, namely Special Lessons and Hifdz Subjects. The existence of this religious program is to provide good benefits for student character shaping. The strategies implemented by the school principal play an important role in ensuring that the regulations support students' character building. The data collection mothed in this research uses interviews, observation, and documentation. The data analysis of this research uses the theory commonly used in qualitative research but with an updated theory from Miles, Hubarman and Saldana, namely Data Condensation. The results showed that the principal has implemented various effective strategies in developing religious programs at school. Including First, making clear and structured regulations. Second, the consistent application of reward and punishment system. Third, collaboration with external institutions. This strategy has three main implications. First, it becomes a facility for character knowledge for students. Second, it instills competitive and disciplined character values. Third, improving students' abilities in the field of religion.